STUDI LITERATUR: MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Adelina Damayanti; Sukmawati; St. Fithriani Shaleh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze previous research so as to obtain a summary regarding the influence of the problem based learning model in improving students' critical thinking skills. This research is qualitative research through literature study. The research was carried out through the data collection stage from library sources. This research classifies data based on a survey formula. In the advanced stage, data processing or citing references is carried out, presented as research results, abstracted into complete information, and interpreted into findings to draw conclusions. The results of the literature study show that the problem based learning model can improve students' critical thinking abilities.